Not Achieving Sustained Viral Eradication of Hepatitis C Virus After Treatment Leads to Worsening Patient-reported Outcomes. (5th April 2019) - Younossi, Zobair M; Stepanova, Maria; Jacobson, Ira; Muir, Andrew J; Pol, Stanislas; Zeuzem, Stefan; Younes, Ziad; Herring, Robert; Lawitz, Eric; Younossi, Issah; Racila, Andrei
Abstract: Background: The causative relationship between the clearance of infections and long-term, health-related quality-of-life (HRQL) improvements in patients with hepatitis C virus (HCV) has been generally accepted. The aim of this study was to assess long-term HRQL trends in HCV patients who did not achieve sustained virologic responses (SVRs) after treatment with direct-acting antivirals. Methods: HCV patients who completed treatment in clinical trials and did not achieve SVRs were enrolled in a long-term registry (#NCT01457768). HRQL scores were prospectively collected using the short form–36 instrument (8 HRQL domains and 2 summary scores). Results: There were 242 patients included: they had a median age of 54 years (standard deviation ± 8 years), 85% were male, and 38% had cirrhosis. Before treatment, patients' HRQL scores were similar to the general population norms (all 1-sided P > 0.05), but were followed by significant decreases by the end of treatment (−3.4 to −6.2 points; P < .05 for 5/8 HRQL domains and mental summary). By the time subjects entered the registry, all but 1 of the mean HRQL scores had returned to their pretreatment levels ( P > .05). During subsequent periods in the registry, patients experienced further HRQL decrements: up to −9.2 points ( P < .05 for all HRQL domains) at Week 24 and up to −8.3 points ( P < .05 for 5/8 HRQL domains) at Week 48. Although these HRQL decrements were observed regardless of cirrhosis status, they were more pronounced in patients with cirrhosis ( P < .05 for 3/8 HRQL domains). Conclusions: Patients who did not achieve an SVR after treatment experienced worsening HRQL scores in long-term follow-ups. Retreatment of these patients will be important not only to improve their clinical outcomes, but also their quality of life. Abstract : Patients with chronic hepatitis C who did not achieve virologic clearance after treatment experienced worsening of their quality-of-life scores in long-term follow-ups. Retreatment may improve both their clinical outcomes and overall well-being.